Health Workforce Policy in Turkey : Recent Reforms and Issues for the Future - Vujicic, Marko (World Bank, Washington, DC, 2013)
The health status of the Turkish population has improved significantly over the past few decades, accompanying improvements in the scale and functioning of the health-care system. Impressive progress has been made in expanding financial protection to the population through expansions in the breadth and depth of health insurance coverage combined with service delivery reforms to improve equity in access to health services. This note summarizes the main developments in the area of health workforce policy and how these have affected key health workforce performance outcomes. Specifically, the main objectives are to: (i) summarize trends in key health workforce outcomes; (ii) compare health workforce outcomes in Turkey to Organization for Economic Co-operation and Development (OECD) and other countries; (iii) discuss the impact of recent reforms in the health sector on health workforce outcomes; and (iv) highlight key health workforce policy issues for the future.